1998
DOI: 10.1183/09031936.98.11020377
|View full text |Cite
|
Sign up to set email alerts
|

Catalase, myeloperoxidase and hydrogen peroxide in cystic fibrosis

Abstract: aaIn cystic fibrosis (CF), the most common autosomal recessive disorder of white populations, abnormal exocrine gland secretions lead to persisting endobronchial bacterial infections [1]. Consequently, large numbers of polymorphonuclear leukocytes (PMN) are recruited to the infected airways where PMN activation and lysosomal enzyme release occur [2]. In particular PMN-elastase (PMN-Ela) has been implicated in chronic lung destruction [2], the major cause of morbidity and mortality in CF, and, consequently, tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 32 publications
(46 reference statements)
6
39
0
1
Order By: Relevance
“…In this study in CF-children with acute infective pulmonary exacerbations higher levels were found than in healthy children [21], and a significant decrease of serial exhaled H 2 O 2 levels in the course of treatment with antibiotics was also found. The observed H 2 O 2 concentrations at the end of the treatment period are similar to those found previously in healthy children [21], and are in agreement with the results of stable CF-adults [22,29]. Thus, exhaled H 2 O 2 may not be a suitable marker of airway inflammation in stable CFpatients, but is of potential value to monitor the effect of anti-inflammatory treatment for exerbations.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study in CF-children with acute infective pulmonary exacerbations higher levels were found than in healthy children [21], and a significant decrease of serial exhaled H 2 O 2 levels in the course of treatment with antibiotics was also found. The observed H 2 O 2 concentrations at the end of the treatment period are similar to those found previously in healthy children [21], and are in agreement with the results of stable CF-adults [22,29]. Thus, exhaled H 2 O 2 may not be a suitable marker of airway inflammation in stable CFpatients, but is of potential value to monitor the effect of anti-inflammatory treatment for exerbations.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, markers of inflammation like H 2 O 2 and NO that can be obtained easily and repeatedly are potentially important for monitoring CF lung disease. Exhaled H 2 O 2 levels in adult CF-patients were investigated earlier and appeared not to be significantly different from those of healthy controls [22,29]. In this study in CF-children with acute infective pulmonary exacerbations higher levels were found than in healthy children [21], and a significant decrease of serial exhaled H 2 O 2 levels in the course of treatment with antibiotics was also found.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…A massive number of neutrophils and macrophages are attracted to infection sites, releasing MPO and H 2 O 2 (30) along with other bactericidal and inflammatory agents. MPO activity is known to inflict severe injuries on airway epithelial cells (20), as well as to stop ciliary beating (H 2 O 2 is also known to inhibit ciliary beating) (39,40). Cilia normally propel pathogens out of the airways, and their impairment would allow bacteria to remain and develop infection (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Montuschi (54 ) reviewed EBC analyses in patients with COPD and listed related breath markers, including H 2 O 2 , eicosanoids (leukotrienes, prostanoids, and isoprostanes), NO-derived products (S-nitrosothiols, nitrite, and nitrate), pH, aldehydes, and others. Moreover, CO has also been studied as a breath marker of asthma (55)(56)(57) and CF (58,59 ); H 2 O 2 as a breath marker of asthma (60,61 ), COPD (62,63 ), and CF (64,65 ); isoprostanes as breath markers of asthma (66 ), COPD (67 ), and CF (68 ); and nitrite/nitrate as breath markers of asthma (69 ) and CF (70,71 ).…”
Section: Lung Diseasesmentioning
confidence: 99%